Correlations Between Body Composition Indicators and Performance in Sprint and Agility Tests Among Handball Referees - CIOBANU, Ștefan; ABALAȘEI, Beatrice Aurelia (Studia Universitatis Babeș-Bolyai. Educatio artis gymnasticae, 2025)
Introduction: Refereeing plays a decisive role in the development of handball games, as referees enforce the rules of the game and facilitate the functioning of the other components, essential to success. To remain consistently prepared, referees must maintain optimal physical condition to support both essential and complementary motor abilities. Objectives: This study aimed to investigate the correlations and regression models between body composition variables and performance in sprint and agility tests among handball referees. Methods: A sample of 12 referees underwent anthropometric assessments using bioelectrical impedance analysis (Tanita MC-580) to explore the correlations between body composition and performance in sprint and agility tests. Statistical analyses included correlation and regression tests to identify significant predictors. Results: The findings indicate a positive correlation between sprint speed and agility, and a negative correlation between sprint speed and bone mass. Conclusions: Despite the limited sample size, the findings suggest that fat-free mass (FFM) and fat mass (FM) influence referees’ physical performance. Further research on larger samples is recommended to validate these results. Article history: Received 2025 May 29; Revised 2025 July 14; Accepted 2025 July 16; Available online 2025 July 30; Available print 2025 August 30